(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2013)
في هذا البحث استطعنا التوصل إلى طريقة تعطي أعداد سالم انطلاقا من أعداد بيزو ، وقدمنا مجموعة من الأمثلة، كما تمكنا من اكتشاف بعض أعداد سالم الصغرى الجديدة , بالإضافة إلى أننا درسنا مجموعة أعداد سالم الواقعة في مجال حقيقي، و توصلنا الى الشرط الواجب أن تحققها أمثال منشورتايلور في جوار الصفر للدالة الكسرية المتعلقة بعدد بيزو حتى ينتج عنه أعداد سالم تقع في مجال حقيقي مفروض In this research, we have put an algorithm which gives Salem Numbers starting from Pisot Number and we have been able to give a few examples and discover some newSmall Salem Numbers. Beside that we have studied the intersection of Salem Numbers with a real interval and put the condition that must be provided by the coefficients of the expansion of the fractional function related to a Pisot Number in order to give Salem Numbers in a certain interval